Activation of Neurotensin Receptor 1 Facilitates Neuronal Excitability and Spatial Learning and Memory in the Entorhinal Cortex: Beneficial Actions in an Alzheimer's Disease Model - Xiao, Zhaoyang (Society for Neuroscience, 2014)
Neurotensin (NT) is a tridecapeptide distributed in the CNS, including the entorhinal cortex (EC), a structure that is crucial for learning and memory and undergoes the earliest pathological alterations in Alzheimer's disease (AD). Whereas NT has been implicated in modulating cognition, the cellular and molecular mechanisms by which NT modifies cognitive processes and the potential therapeutic roles of NT in AD have not been determined. Here we examined the effects of NT on neuronal excitability and spatial learning in the EC, which expresses high density of NT receptors. Brief application of NT induced persistent increases in action potential firing frequency, which could last for at least 1 h. NT-induced facilitation of neuronal excitability was mediated by downregulation of TREK-2 K(+) channels and required the functions of NTS1, phospholipase C, and protein kinase C. Microinjection of NT or NTS1 agonist, PD149163, into the EC increased spatial learning as assessed by the Barnes Maze Test. Activation of NTS1 receptors also induced persistent increases in action potential firing frequency and significantly improved the memory status in APP/PS1 mice, an animal model of AD. Our study identifies a cellular substrate underlying learning and memory and suggests that NTS1 agonists may exert beneficial actions in an animal model of AD.